Structural and Mechanical Properties of Cl- and Br-doped WSe2 Monolayer for Possible Application in Flexible Photovoltaic Panel: An ab-initio study - Mohammed A; Shu’aibu A; Abdu, Sadiq G.; M. Aliyu, Muhammed; Lawal, Abdullahi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This work investigates the structural and mechanical properties of Chlorine- and Bromine-doped WSe2 Monolayers. Our result reveals that the introduction of Chlorine impurities into the pristine WSe2 monolayer is thermodynamically more promising under Se-rich conditions due to the smaller formation energy and may be the most favorable replacement of Se. Further, it is noted that the calculated elastic constants are all positive and they certify the Born stability criteria for monolayer, which is an indication that all the doped materials are mechanically stable, show considerable resistance to linear compression and behave in a brittle manner. Therefore, our findings suggest a strategy to tailor the mechanical properties of the studied materials by doping their structural phases for various applications. The study of mechanical properties of 2D materials may further advance the development of ultrathin flexible wearable photovoltaic solar panels and other electromechanical systems.